Generation of Formal Model Metrics for MOF based Domain Specific Languages - Hein, Christian; Engelhardt, Marcus; Ritter, Tom; Wagner, Michael (Electronic Communications of the EASST, 2010)
The assessment of quality in a software development process is vital for the quality of the final system. A number of approaches exist, which can be used to determine such quality properties. In a model-driven development process models are the primary artifacts. Novel technologies are needed in order to assess the quality of those artifacts. Often, the Object Constraint Language is used to formulate model metrics and to compute them automatically afterwards. This paper describes an approach for the generation of model metrics expressed as OCL statements based on a set of generic rules. These rules can be applied on any domain specific modeling languages for creating a basic set of metrics which can be tailored for the specific needs of a development process. The paper also briefly describes a prototype of a tool for the generation, computation, and management of these model metrics by using the Software Metrics Meta-model - SMM.